Ecological Park for whom? The Case of the Ecological Park of Bodocongó in Campina Grande - PB - Souza , Suzane Bezerra Farias de; Barros Filho , Mauro Normando Macêdo; Anjos , Kainara Lira dos; Villarim , Lizia Agra (National Journal of City Management, 2023)
The Bodocongó Reservoir, an important memory of the city of Campina Grande, received an ecological park on its banks in 2017 in celebration of its 100th anniversary of construction. It was the result of a millionaire investment from the government of Paraíba in partnership with the city of Campina Grande and since then it has been criticized mainly about the high value invested to the detriment of its apparent underutilization. This work seeks to understand more about the general characteristics of the park, analyzing the program of needs and its relationship with the profile of the users. The method used was investigation through morphological analysis, in order to understand if it meets the needs of the users, being provided with urbanity which is a characteristic that leads the users to appropriate the space and, consequently, its vitality, which would be the presence of people at various times using the space. As a result, it was found that the park has a wide variety of equipment, especially sports, for various age groups and has been improving the quality of life of both the neighborhood and the Campina Grande residents as a whole, while needing improvements in its physical structure, mainly maintenance. Finally, this work seeks to increasingly encourage public leisure, which presents an undeniable importance in society, as it directly influences the preservation of the environment and the well-being of the population. In addition, encourage social and sports practices that often find themselves in scarcity and/or in poor conditions of use, repelling even more users.